Probing the effect of PEG-DNA interactions and buffer viscosity on tethered DNA in shear flow - Fatema Tuz Zohra; Huda Al-Zuhairi; Jefferson Reinoza; HyeongJun Kim; Andreas Hanke (PLoS ONE, 2025)
DNA flow-stretching is a widely employed, powerful technique for investigating the mechanisms of DNA-binding proteins involved in compacting and organizing chromosomal DNA. We combine single-molecule DNA flow-stretching experiments with Brownian dynamics simulations to study the effect of the crowding agent polyethylene glycol (PEG) in these experiments. PEG interacts with DNA by an excluded volume effect, resulting in compaction of single, free DNA molecules in PEG solutions. In addition, PEG increases the viscosity of the buffer solution. By stretching surface-tethered bacteriophage lambda DNA in a flow cell and tracking the positions of a quantum dot labeled at the free DNA end using total internal reflection fluorescence (TIRF) microscopy, we find that higher PEG concentrations result in increased end-to-end length of flow-stretched DNA and decreased fluctuations of the free DNA end. To better understand our experimental results, we perform Brownian dynamics simulations of a bead-spring chain model of flow-stretched DNA in a viscous buffer that models the excluded volume effect of PEG by an effective attractive interaction between DNA segments. We find quantitative agreement between our model and the experimental results for suitable PEG-DNA interaction parameters.